A New-Institutional Analysis of Inclusion Policy Enactment in Teacher Education: A Case from Ontario - Massouti, Ayman (Canadian Journal of Educational Administration and Policy / Revue canadienne en administration et politique de l’éducation)

(untitled) (Department of Educational Administration, University of Saskatchewan, 2021)
This qualitative single case study aimed to examine the logics of one teacher education program towards preparing pre-service teachers for inclusive teaching from the perspectives of the program’s coordinators. In particular, the study aimed to understand the practices of these coordinators and how these practices are influenced by inclusive education and teacher education policies. This examination would reveal how education policies are enacted in this particular case. New-Institutionalism (NI) theory (DiMaggio & Powell, 1991) constituted the theoretical framework that guided the methodology as well as the analysis of the findings. The study revealed that the coordinators’ understanding and practices around the existing inclusion and teacher education policies emerge from their own experiences in this particular program, intermingled with their beliefs about how inclusion should be enacted in teacher education and schools. Key findings included coordinators developing inclusive mindsets among pre-service teachers, negotiating their logics towards inclusion through modeling inclusive teaching practices in the university classroom, and engaging them in critical discussions around inclusion policy practice in schools, and coordinators calling for a curriculum policy change. Recommendations for future teacher education programming in response to the evolving inclusive education are offered.